Effect of the level of task abstraction on the transfer of knowledge from virtual environments in cognitive and motor tasks - del Rocío Hernández-Castañón, Viviana; Castillo-Ávila, Arlem Aleida; Reyes-Meza, Verónica; Bianchi-Berthouze, Nadia; Morán, Alberto L.; Orihuela-Espina, Felipe (Frontiers in Behavioral Neuroscience, 2023)
Background. Virtual environments are increasingly being used for training. It is not fully understood what elements of virtual environments have the most impact and how the virtual training is integrated by the brain on the sought-after skill transference to the real environment. Aim. In virtual training, we analyzed how the task level of abstraction modulates the brain activity and the subsequent ability to execute it in the real environment and how this learning generalizes to other tasks. Hypothesis. The training of a task under a low level of abstraction should lead to a higher transfer of skills in similar tasks, but the generalization of learning would be compromised, whereas a higher level of abstraction facilitates generalization of learning to different tasks but compromising specific effectiveness. Method. Twenty-five participants were trained and subsequently evaluated on a cognitive and a motor task following training regimes, considering real vs virtual training and low vs high task abstraction. Performance scores, cognitive load and electroencephalography signals were recorded. Transfer of knowledge was assessed by comparing performance scores in the virtual versus real environment. Results. The performance to transfer the trained skills showed higher scores in the same task under low abstraction, but the ability to generalize the trained skills was manifested by higher scores under high level of abstraction in agreement with our hypothesis. Spatiotemporal analysis of the electroencephalography revealed higher initial demands of brain resources which decreased as skills were acquired. Conclusions. Task abstraction during virtual training influences how skills are assimilated at the brain level and modulates its manifestation at the behavioural level. We expect this research to provide supporting evidence to improve the design of virtual training tasks.